Examining patient's right to information in informed consent / Lydia Aiseah Ariffin - Ariffin, Lydia Aiseah (2018)
Informed consent has been recognised to be an essential part of clinical practice as it gives ethical and legal legitimacy to all medical interventions. The human rights movement and common law gives patients the right to be provided adequate information prior to authorising a medical procedure. There is no universal standard on the amount and type of information that a patient is entitled to and is needed to be adequately disclosed. This study is an effort to ensure that information disclosure is as adequate as possible for all patients by reviewing and analysing the human rights documents, consent guidelines and common laws. This study proposed 10 types of information that will assist in adequate information disclosure and patients are entitled to these information in order to evaluate decision to consent. The recommended types of information are: (1) diagnosis, prognosis and its uncertainties; (2) nature of proposed medical intervention; (3) expected benefit of proposed medical intervention; (4) potential risk of proposed medical intervention; (5) alternative to proposed medical intervention; (6) progress of proposed medical intervention; (7) opportunity for second medical opinion and seek further details; (8) additional consent from other family member for competent patient; (9) costs of proposed and alternative medical intervention; and (10) person responsible for the medical intervention performance. Prior to disclosure, the doctors are recommended to obtain adequate information on patient's background and history to estimate the depth and amount of information to disclose. The practice of informed consent will be more feasible and productive when the patients are familiar with their right to information and being responsible to assist the doctors in ensuring adequacy of information in informed consent.